China, Government Expenditure, Growth, Poverty, and Infrastructure, 1952-2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
This dataset provides information on key economic indicators, agricultural output and inputs, public investments, poverty, and various social indicators in China. Cross-section (29 provinces) and time-series (50 years from 1952 to 2001) data are included in this dataset. The dataset consists of 50 variables altogether, including agricultural and nonagricultural GDP, agricultural labor, agricultural output, agricultural population, arable land, share of rural population with college education, total telecommunication expenditures (rural and urban), draft animals, education expenditures, rural electricity consumption, total expenditures in electricity construction, fertilizer use in pure nutrients, rural illiteracy rate, machinery use, official rural poverty rates, rural education expenditures, agricultural research expenditures, road construction expenditures, rural telephones, etc.